Delivering AI-based mental healthcare to build resilience in Ukrainian servicemen and veterans: a call for cooperation - Assonov, Dmytro; Voznitsyna, Kseniia; Sirenko, Tetiana (Psychosomatic Medicine and General Practice, 2022)
Russian aggression disrupted delivery of mental healthcare services for veterans in Ukraine. These causes required to create some new solutions about artificial intelligence based (AI-based) psychological services for Ukrainian defenders. Specialists from the Centre for veterans’ mental health “Forest Glade” of Ministry of Health of Ukraine have created a Telegram-based bot (Lisova Poliana Bot) to reach the specific needs of veterans and servicemen. Such form of AI-based service achieved positive feedback from soldiers, officers and volunteers and helped to partially unload the psychological service in wartime without excluding the Ukrainian defender from it. Therefore, AI solutions have a potential to be integrated in healthcare system. Given the great potential of artificial intelligence in the provision of services during the war, further comprehensive research and cooperation at the international level can be promising. We invite international researchers to cooperate in creating and delivering AI-based consulting tools for Ukrainian defenders.